Characteristics of Writing Explanation Text Enrichment Book Containing 21st Century Competence for Senior High School Students - Badriyah, Nurul; Zulaeha, Ida; Wagiran, Wagiran (Universitas Negeri Semarang, 2020)
The formation of student personalities that can be developed with writing explanatory texts enrichment book containing 21st century competencies includes aspects of knowledge, skills, and personality that are integrated with 21st century competencies that students must master. This study aims to analyze the need for enrichment book development in writing explanatory text with 21st century competencies and the characteristics of enrichment book development for writing explanatory text with 21st century competence. The research method uses the Research and Development and uses six steps out of ten steps in the R&D method. The results obtained from this study were an analysis of the needs of students and teachers which were grouped based on question aspects, namely (1) material and content needs, (2) 21st century competency content needs, (3) presentation needs, (4) language needs. and (5) legibility and graphics needs. This needs analysis is to determine the tendency of the needs of students and teachers to the form of the enrichment book being developed. Then, the characteristics of the enrichment book are writing explanatory texts containing 21st century competencies according to the perceptions of students and teachers in accordance with the principles of content feasibility, presentation feasibility, linguistic feasibility, and graphic feasibility. In addition, teachers and students are very in accordance with the form of the book that is being made easy to carry. Therefore, the development of an enrichment book to write explanatory texts containing 21st century competencies is in accordance with the wishes of teachers and students in using a learning resource.